Strategi Pengembangan Usaha UMKM Royal Bubble Seberang Kota Jambi di Era Digital - Muhammad Rivandi Akbar; Dahmiri Dahmiri; Dwi Kurniawan (JURNAL RISET MANAJEMEN (JURMA), 2025)
This study aims to develop a business development strategy for the UMKM Royal Bubble Seberang Kota Jambi in the digital era using a SWOT analysis. The research findings indicate that, from an internal perspective, Royal Bubble possesses greater strengths than weaknesses, with a positive difference of 0.45. However, from an external perspective, opportunities are smaller than threats, with a negative difference of -0.18. The position of UMKM Royal Bubble falls into quadrant II of the SWOT matrix, indicating that although the business has significant strengths, there are external threats that need to be addressed. The recommended strategy for business development is to leverage internal strengths to mitigate threats and optimize long-term opportunities through product diversification. Additionally, utilizing digital platforms, improving service quality, and collaborating with various stakeholders are crucial factors in enhancing business competitiveness. By implementing the right strategies, Royal Bubble can strengthen its market position and sustain its business in the digital era.